Issues Of International Relations in A Multinational Country: Solutions And Progress (Experience Of Uzbekistan). - Kholikulov Pirnafas (Periodica Journal, 2024)
The article highlights the issues of preservation of language, customs, traditions and culture, unique values, further development of interethnic relations of more than 130 nations and peoples living in multi-ethnic Uzbekistan during the years of independence. The reasons for the arrival of people of other nationalities in Uzbekistan, hospitality and tolerance of the Uzbek people are revealed. The article also notes that equal conditions have been created in Uzbekistan for the preservation of the national identity of ethnic groups, with 138 national cultural centers coordinated by a State organization, the International National Centre, eight languages are taught in schools, and the media are published in 12 languages. All this is explained by the fact that there is mutual understanding in inter-ethnic relations in Uzbekistan and that all the nations and peoples living in the country live in peace and harmony on the basis of the idea that “Uzbekistan is our common home”.
Keywords: state policy in the field of interethnic relations; migration; concept